Mask Use Depends on the Individual, Situation, and Location—Even Without COVID-19 Transmission: An Observational Study in Shanghai - English, Alexander S.; Li, Xiaoyuan (Frontiers in Psychology, 2021)
COVID-19 has drastically altered people’s mask-wearing behaviors around the world. What is unknown is how long these mask behaviors will last post-COVID? To investigate how individual, situational, and locational factors influence mask use in the absence of community spread of COVID, we conducted an observational study in public areas in the megacity of Shanghai, China. Researchers coded people’s mask use in various suburban and urban districts and outdoor and indoor locations with and without mask requirements. Firstly, even without any local transmissions in more than 40 days, 62% of the sample (N = 1,282) still wore masks in public places. The data showed that people in more urban areas wore masks more often and that people wore masks in places where it was mandated. Women also wore masks more than men, and older people complied more with mask enforcement policies. We found that more densely populated districts and areas with more inflow of non-locals also predicted more mask use. We argue that the pandemic has long-lasting effects on human behavior like mask usage and reflects individuals’ continual conformity to new social norms.